UNSUR AQIDAH ISLAM DALAM ADAT TURUN MANDI BAYI STUDI KASUS: DESA MUARA KIAWAI KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT - Dahlia Lubis; Faisal Riza; Ainul Huda (UIN Sumatera Utara, 2020)
The tradition of taking a bath in the Minangkabau community in MuaroKiawai Village is a tradition that has been passed down from generation to generation, and is a tradition to give thanks to Allah SWT for a newborn, before the implementation of the tradition. including preparing various food menus, preparing betel and areca baths. The implementation process involves the bako and the baby's family. The purpose of study is too see the values contained in the tradition of taking a bath in the village of MuaroKiawai are: introducing children to the surrounding environment, after the big children are expected to become illuminators for society, religion and nation, being brave in upholding the truth can be successful people. The type of this jurnal research is a qualitative research model with descriptive methods by means of observation or observing whether the tradition of taking a bath in the Minangkabau Community in Muaro Kiawai deviates from Islamic Aqidah as the purpose of this Jurnal is made.Keywords: Tradition, Adat and Baby Bathing, Elements of Islamic Aqidah.